2011
DOI: 10.4236/jsea.2011.411071
|View full text |Cite
|
Sign up to set email alerts
|

A Petri Net Model for Part Sequencing and Robot Moves Sequence in A 2-Machine Robotic Cell

Abstract: This paper deals with part sequencing and optimal robot moves sequence in 2-machine robotic cells according to Petri net graph. We have assumed that the robotic cell is capable of producing same and different parts. We have considered a new motion cycle for robot moves sequence which is the development of existing motion cycles in 2-machine robotic cells. The main goal of this study is to minimize the cycle time by determining the optimal part sequencing and robot moves sequence in the robotic cell. So, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…They also proposed two metaheuristic algorithms-particle swarm optimization (PSO) and simulated annealing (SA)-to optimize part sequencing. Moreover, Fathian et al [56] suggested a mathematical programming model based on PNs to minimize cycle time when producing either similar or different parts by optimizing the part sequencing in the robotic cell. Their study was limited to a two-parallel-machine cell and assumed the existence of feasible robot move cycles.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…They also proposed two metaheuristic algorithms-particle swarm optimization (PSO) and simulated annealing (SA)-to optimize part sequencing. Moreover, Fathian et al [56] suggested a mathematical programming model based on PNs to minimize cycle time when producing either similar or different parts by optimizing the part sequencing in the robotic cell. Their study was limited to a two-parallel-machine cell and assumed the existence of feasible robot move cycles.…”
Section: Literature Surveymentioning
confidence: 99%
“…Fathian et al [56] presented a TPN graph to model part sequencing and optimal robot movement sequencing in a robotic manufacturing cell with two identical machines and one robot. They also proposed two metaheuristic algorithms-particle swarm optimization (PSO) and simulated annealing (SA)-to optimize part sequencing.…”
Section: Literature Surveymentioning
confidence: 99%
“…Moreover, Gultekin et al [21] studied the scheduling problem of a 2-machine robotic cell. Fathian et al [22] formulated a Petri Net model to get an optimal schedule of part sequencing and robot moves in a 2-machine robotic cell.…”
Section: Related Literaturementioning
confidence: 99%
“…In literature different methods have been developed to obtain an optimal or near optimal schedule for the problems which have some similarities with the current research problem. For example, branch and bound algorithm [19], [36], linear programming [37], [38], heuristics [23]- [25], [29], some other metaheuristics [27], [39]- [43], and other methods specialized for related problems [22], [31], have been used and presented for scheduling of jobs with material handling devices in different manufacturing environment. Tabu search [44] is a metaheuristic method which can guide a local search solution to explore the solution space within the constraint of tabu list.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation